Sodium nitrite promotes atherosclerosis via IL-1β: Network toxicology and machine learning insights - Haobo Yang; YunFeng Yu; Yonghui Zhang; YaNan Bai; YaRu Shi; WeiXiong Jian (PLoS ONE, 2026)
Background Atherosclerosis (AS) is a major global health burden. Sodium nitrite, a common environmental and dietary contaminant, has been implicated in promoting AS, but its systematic molecular mechanisms remain unclear. Methods and results To address this gap, we integrated network toxicology, machine learning, transcriptomics, molecular docking, and molecular dynamics simulations. Disease-related targets were first identified from public databases, and four core candidates—IL-1β, IL6, PTK2, and NOS3—were prioritized using machine learning approaches. Molecular docking confirmed strong and stable binding affinities between sodium nitrite and these targets, while molecular dynamics simulations further validated the stability of the sodium nitrite–IL-1β complex. Moreover, immune infiltration analysis revealed a significant increase in monocyte/macrophage infiltration within AS plaque tissues, suggesting that sodium nitrite–related targets are associated with immune microenvironment changes in AS. Conclusion Collectively, this study proposed an adverse outcome pathway (AOP) framework linking sodium nitrite exposure to atherosclerosis, providing hypothesis-generating mechanistic insights for future experimental validation.